2015
DOI: 10.17306/j.afs.2015.3.25
|View full text |Cite
|
Sign up to set email alerts
|

Effect of germination time on proximate analysis, bioactive compounds and antioxidant activity of lentil (Lens culinaris Medik.) sprouts

Abstract: Background. The lentil plant, Lens culinaris L., is a member of the Leguminoceae family and constitutes one of the most important traditional dietary components. The purpose of the current study was to investigate the effects of sprouting for 3, 4, 5 and 6 days on proximate, bioactive compounds and antioxidative characteristics of lentil (Lens culinaris) sprouts. Material and methods. Lentil seeds were soaked in distilled water (1:10, w/v) for 12 h at room temperature (~25°C), then kept between thick layers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
70
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(100 citation statements)
references
References 82 publications
(70 reference statements)
13
70
0
7
Order By: Relevance
“…Similar observations were made by Fouad and Rehab (2015), which studied the effects of germination time on lentil sprouts. They observed an increase of TPC during germination with the maximum level at 5-day lentil sprouts, followed by a decrease, which they proposed as due to mobilization of stored phenolics by the activation of enzymes like polyphenol oxidase (Fouad and Rehab, 2015). Activation of polyphenol oxidase could also explain the decrease of TPC in the 7-day broccoli and 9-day cauliflower sprouts of the present work.…”
Section: Total Phenolic Contentsupporting
confidence: 79%
“…Similar observations were made by Fouad and Rehab (2015), which studied the effects of germination time on lentil sprouts. They observed an increase of TPC during germination with the maximum level at 5-day lentil sprouts, followed by a decrease, which they proposed as due to mobilization of stored phenolics by the activation of enzymes like polyphenol oxidase (Fouad and Rehab, 2015). Activation of polyphenol oxidase could also explain the decrease of TPC in the 7-day broccoli and 9-day cauliflower sprouts of the present work.…”
Section: Total Phenolic Contentsupporting
confidence: 79%
“…Fouad and Rehab (2015) also found that germination caused a significant increase in DPPH radical scavenging activity, total phenolic content and free amino acid content in germinated lentils (p≤0.05). Similar results were also found in germinated mung bean (Wongsiri et al, 2015) These results also demonstrated that the influence of extraction solvent on measured antioxidant activities of rice bean extracts was remarkable.…”
Section: Effect Of Extraction Solvents On Antioxidant Activities Of Rmentioning
confidence: 76%
“…An increase in protein content was observed in germinated lupin (Rumiyati et al 2012). In contrast, Fouad and Rehab (2015) reported a reduction in sulfur amino acids and increased lysine in germinated lentils. Germination and enzymatic hydrolysis of the protein can affect the amino acid profile.…”
Section: Protein Content and Composition Of Pulse Cropsmentioning
confidence: 86%